How pet food selection attributes influence customer satisfaction and loyalty: evidence from South Korea - Lee, Ji-eun (Frontiers in Nutrition, 2025)
BackgroundThis study examined the impact of pet food selection attributes, including price, quality, reliability, and convenience, on customer satisfaction and loyalty in South Korea’s evolving pet food market. The pet industry in South Korea is expanding rapidly, driven by changes in demographics like the rise of single-person households and aging populations. It is essential to understand consumer preferences in pet food attributes.MethodsA survey of 365 pet owners was conducted, and data were analyzed using path analysis.ResultsThe analysis showed that reliability and convenience play a significant role in increasing customer satisfaction and loyalty, while price and quality do not have a significant effect. Consumers value trust in product origins, brand credibility, and practical features like easy-to-store packaging. These results underscore the importance of attributes that simplify daily routines and build trust in pet food products.DiscussionThese findings stress the importance of transparency in production processes and consumer-oriented product designs that meet modern demands for convenience. By prioritizing these attributes, pet food manufacturers can better align their products with changing consumer expectations, improving loyalty and strengthening their competitive position in a dynamic market. This study offers insights into how selection attributes affect customer satisfaction and loyalty, with practical implications for product development and marketing strategies in the rapidly growing pet food sector. However, the study is limited by its sample representativeness and the scope of analyzed attributes, suggesting considerable scope for future research to broaden demographic coverage and explore additional influencing factors.